Nutrient Removal Process and Cathodic Microbial Community Composition in Integrated Vertical-Flow Constructed Wetland – Microbial Fuel Cells Filled With Different Substrates - Zhong, Fei; Yu, Chunmei; Chen, Yanhong; Wu, Xue; Wu, Juan; Liu, Guoyuan; Zhang, Jian; Deng, Zifa; Cheng, Shuiping (Frontiers in Microbiology, 2020)
Abstract: An integrated vertical-flow constructed wetland-microbial fuel cell system (CW-MFC), consisting of an up-flow chamber and a down-flow chamber, was constructed to treat synthetic sewage wastewater. The performance of CW-MFCs filled with different substrates [i.e., ceramsite (CM-A), quartz (CM-B), and zeolite (CM-C) granules] under various hydraulic retention times (HRTs, 7.6 d, 4.0 d, and 2.8 d) was evaluated. Efficient and stable nitrogen (N) and phosphorus (P) removals were observed in CM-A under different HRTs, while the voltage outputs of the CW-MFCs was greatly reduced as the HRTs decreased. With an HRT of 2.8 d, the ammonium (NH4+-N) and orthophosphate (PO43--P) removal efficiencies in CM-A were as high as 93.8% and 99.6%, respectively. Bacterial community analysis indicates that the N removal in the cathode area of CM-A could potentially benefit from the appearance of nitrifying bacteria (e.g., Nitrosomonas and Nitrospira) and relatively high abundance of denitrifiers involved in simultaneous nitrification and denitrification (e.g., Hydrogenophaga, Zoogloea, and Dechloromonas) and denitrifying sulfide removal (e.g., Thauera). Additionally, the difference in N removal efficiency among the CW-MFCs could be partly explained by higher iron (Fe) content in milled ceramsite granules and higher abundance of denitrifiers with nitrate reduction and ferrous ions oxidation capabilities in CM-A compared with that in CM-B and CM-C. Efficient PO43--P removal in CM-A was mainly ascribed to substrate adsorption and denitrifying phosphorus (P) removal. Concerning the substantial purification performance in CM-A, ceramsite granules could be used to improve the nutrient removal efficiency in integrated vertical-flow CW-MFC.